Geographic Information Systems (GIS)-Based Visualization for Black Spot Identification on the Karanganyar-Matesih Road - Magfirona, Alfia; Aida, Pipit Mosque; Hidayati, Nurul; Azmi, Hafidzul (Universitas Ibn Khaldun Bogor, 2025)
The relatively busy traffic movement on Jalan Karanganyar-Matesih causes various transportation problems, including increasing accidents. This study aims to analyze the characteristics of accidents, factors causing accidents, and accident-prone locations (black spots) in Jalan Karanganyar-Matesih which are visualized using A Geographic Information System (GIS). This study uses primary data (road geometric data) and secondary data (data on accident characteristics and factors causing accidents). Black spots can be analyzed and identified by using the Accident Equivalent Number (AEK) and the Upper Control Limit (UCL) method. The results of this study are the type of collision in accidents that often occur on Jalan Karanganyar-Matesih is front-side as many as 72 (42%) incidents, the class of victims with the highest number is minor injuries with a total of 191 (73%) people, the gender and age of drivers who are often involved are male, namely 241 (82%) people, the age of the majority of drivers is 18-30 as many as 128 (43%) people, the type of vehicle that is often involved in accidents is a motorcycle with a total of 272 (92%) vehicles, and the time of the accident often occurs during the day (12.00-18.00) with a total of 61 (37%) incidents. The main factor causing accidents on Jalan Karanganyar-Matesih is human negligence which totals 154 (94%) incidents. The results of the calculation analysis that has been carried out using the AEK and UCL methods obtained 7 segment locations that have AEK values ​​> UCL so that they are indicated to be black spot locations.